Benson Relaxation Therapy Effectively Reduces Blood Pressure In Other Adult With Hypertension: A Pre-Experimental Study - Sutrisno Sutrisno (Masker Medika, 2024)
Introduction: The prevalence of hypertension in the elderly continues to increase both globally and nationally. Hypertension in the elderly, if not treated properly, can certainly cause several complications ranging from heart disease to stroke and death. Unstable blood pressure is one of the negative effects of hypertension in the elderly, therefore, efforts are needed to control fluctuating blood pressure as a preventive measure. One therapy that can be used to control blood pressure is pharmacological and non-pharmacological therapy. The effects caused by pharmacology can have negative consequences for the elderly, therefore a non-pharmacological based therapy was developed, namely Benson relaxation therapy. The advantage of Benson relaxation therapy is that apart from being able to stabilize blood pressure, Benson relaxation therapy is also done easily and can be done by anyone at any time, and does not require time and money. Research objectives: This study aims to determine the effect of knowing Benson relaxation on blood pressure before and after in the elderly. Method: This research uses a pre-experimental design with a research plan of one group pre-post test design. This research was conducted on 8 - 10 June 2023. The population of this research were victims of post-flood disasters with a sample size of 50 respondents. Result:The results showedthat the systolic blood pressure value after the intervention was obtained was a median of 162.00 mmHg with a standard deviation value of 10,488. Meanwhile, the diastolic blood pressure value after the median intervention was 73.00 mmHg with a standard deviation value of 10.024. Discussion: There is a significant effect of the Benson relaxation technique on blood pressure in the elderly with a p value of 0.000 (p<0.05).